1937
DOI: 10.1084/jem.65.2.177
|View full text |Cite
|
Sign up to set email alerts
|

The Production of Blood Platelets in the Lungs

Abstract: The present investigation had its origin in the suggestion that the blood of the emergent vein of the organ or organs in which platelet production is taking place should show a higher platelet count than the venous blood of other organs. In order to carry out this idea it was essential to find a satisfactory method of counting both platelets and erythrocytes in samples of blood removed from the veins by means of a syringe. Such a method was devised. It is described in detail below. In applying this method to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
1
3

Year Published

1940
1940
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(81 citation statements)
references
References 4 publications
4
72
1
3
Order By: Relevance
“…In the healthy adult animals, passage of mixed venous blood through the pulmonary capillary bed resulted in a significant reduction in MK count by 65%, which was associated with a 34% increase in platelet count. These findings were consistent with those previously reported by other investigators (21,23,24), and provided further evidence that the lung is an important site for MK fragmentation and platelet release. A similar albeit slightly lesser prepulmonary and postpulmonary gradient in MK and platelet counts was also observed in the term and preterm neonatal pups, thus confirming the role of the lung in platelet release in the newborns.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the healthy adult animals, passage of mixed venous blood through the pulmonary capillary bed resulted in a significant reduction in MK count by 65%, which was associated with a 34% increase in platelet count. These findings were consistent with those previously reported by other investigators (21,23,24), and provided further evidence that the lung is an important site for MK fragmentation and platelet release. A similar albeit slightly lesser prepulmonary and postpulmonary gradient in MK and platelet counts was also observed in the term and preterm neonatal pups, thus confirming the role of the lung in platelet release in the newborns.…”
Section: Discussionsupporting
confidence: 93%
“…The presence of MK cells in the human lungs was described by Aschoff over 100 years ago (20). Subsequently, a number of studies have demonstrated that MK were greater in abundance and cytoplasmic volume in the central venous (prepulmonary) blood than in the arterial (postpulmonary) blood (21)(22)(23)(24)(25), providing an indirect evidence that these cells are fragmented in the lungs. Studies on patients on cardiopulmonary bypass have shown that the lungs are net removers of MK from the circulation (25).…”
mentioning
confidence: 98%
“…Alternatively, prePLTs may become trapped in the micro-capillaries of the bone marrow, lung and/or spleen where intravascular shear forces can drive PLT production. Indeed, reports of higher PLT counts in post-pulmonary vessels suggests that the lung may be a milieu for terminal PLT formation 15 . Second, we show that twisting microtubule-based forces driving circular-prePLT to barbell-proPLT conversion are governed by two major biophysical properties: microtubule coil diameter and microtubule coil thickness.…”
Section: Discussionmentioning
confidence: 99%
“…The platelets were clumped in large aggregates, and stained poorly with hematoxylin-eosin or eosin-methylene blue. The application of Wright's stain, by the technique of Howell and Donahue (21), resulted in adequate differentiation and readily permitted the identification of these elements. No evidence of necrosis of the vessel wall could be seen at this stage, and the leucocytes both inside and outside of the capillaries and veins appeared intact.…”
Section: The Occurrence Of Leucocyte-platelet Thrombi In Cutaneous Blmentioning
confidence: 99%